Analisis Usaha Penggemukan Sapi Potong Dengan Menggunakan Paradigma Agribisnis (Studi Kasus Pada Peternakan Sapi Potong Molan) di Kecamatan Binjai Barat Kota Binjai Provinsi Sumatera Utara - Ruth Dameria Haloho (AGRIMOR, 2020)
This study aims to determine the Analysis of Molan Cattle Fattening Business Analysis. This research was carried out at the Molan Cattle Fattening Business in Tanjung Jati Village, Binjai District, Binjai City. The research is a case study. The selection of research locations with consideration of the business of Molan Cattle Farming is a profitable business. The data were collected by doing observation and direct interviews. The Data were analysis with descriptive and quantitative method. The results showed the total variable costs incurred 1 409 600 000 IDR, fixed costs amounting to 75,000,000 IDR with 1 950 000 000 IDR in revenues. The profitability value is 31.34%. The results showed the number of cattle fattening as many as 150 heads with income of 465 400 000 IDR. BEP Fattening Molan Cattle Fattening Business is 267,858,142 IDR by maintaining 21 cows. The conclusion of this research is the profitability of Molan Cattle Fattening is 31.34% higher than the interest bank of 6 percent and The Value of BEP as much as 267 858 142 IDR with maintaining 21 tails.